Expectantly managed previable preterm PROM in an IVF conceived DCDA twin pregnancy: first case of longest extended latency in India - Tandulwadkar, Sunita; Mishra, Sneha; Langde, Swapnil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Previable preterm premature rupture of membranes (PPROM) between 14 and 24 weeks of gestation complicates < 1% of pregnancies. Previable PPROM in dichorionic diamniotic (DCDA) twin pregnancies are even rarer, and there is no consensus in the literature on outcomes and management due to scarcity of reports. With the recent advances in obstetrics and neonatal care, expectant management is a ray of hope for such precious pregnancies. We presented a case report of a 27 years old lady with previous two abortions with an IVF conceived DCDA twin pregnancy. We were able to extend the latency period by 95 days with our expectant management with favourable outcomes both mother and the baby. To the best of our knowledge, this is the longest case of successful expectant management of IVF conceived twins with PV-PPROM reported in India.